2016
DOI: 10.1080/23311932.2016.1196808
|View full text |Cite|
|
Sign up to set email alerts
|

Pesticide exposure from fresh tomatoes and its relationship with pesticide application practices in Meru district

Abstract: Tomato pesticides health risk was assessed in Meru district of Arusha region, one of the key tomato producers in Tanzania. Tomato samples and consumption information were collected from 50 farmers using Food and Drug Administration standards and twice administered twenty-four hour recall questionnaire respectively. Analysis for pesticide residues was done using Gas Chromatography Mass Spectrometry. Dietary pesticide exposure was estimated deterministically by combining pesticide residue levels and tomato consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 30 publications
5
36
0
Order By: Relevance
“…6, 7 and 8), which were a major problem in Mwea Irrigation Scheme. Similar results indicating use of insecticides and fungicides to control enormous pests and diseases on tomatoes was reported by Mueke [27] in Mwea sub-county; in Tanzania [30], major horticultural zones in Kenya [18,19], and other African countries [31,32]. (Figs.…”
Section: Pesticide Types Applied On Tomatoes In Mwea Irrigation Schemesupporting
confidence: 86%
See 1 more Smart Citation
“…6, 7 and 8), which were a major problem in Mwea Irrigation Scheme. Similar results indicating use of insecticides and fungicides to control enormous pests and diseases on tomatoes was reported by Mueke [27] in Mwea sub-county; in Tanzania [30], major horticultural zones in Kenya [18,19], and other African countries [31,32]. (Figs.…”
Section: Pesticide Types Applied On Tomatoes In Mwea Irrigation Schemesupporting
confidence: 86%
“…Similar findings were reported by [18] in Kathiani District, Kenya that farmers mainly applied pyrethroids and carbamates on vegetables. WHO class II pesticides are toxic and their residues are likely to remain in the crop when used inappropriately [30]. Toxicological studies [33,34] have revealed that some pesticides (eaten in food) could cause human health effects ranging from short-term, such as headache, nausea and diarrhoea, to long-term effects, such as cancer, teratogenesis and damage to the immune system, among others have been linked to pesticides [7,35,36].…”
Section: Pesticide Types Applied On Tomatoes In Mwea Irrigation Schemementioning
confidence: 99%
“…The statistics tests indicate that there is no significant difference between the two centres when it comes to knowledge of mixing pesticides to achieve sound results. Mixing and loading remain a potential source of pesticide exposures (Kariathi et al, 2016). This is supported by Cornell (1992) study that pesticides must only be issued to staff who has appropriate training.…”
Section: Population That Is Aware Of Procedures For Mixing Categoriesmentioning
confidence: 99%
“…In view of the worries, there is an urgent need to generate more data on levels of pesticide residues in tomato and other food products from Tanzania and use the data to perform a risk assessment to estimate the risk of exposure of pesticide residues in Tanzania. The outcome of the exposure assessment and those of the recent assessment by Kariathi et al (2016) can be used in advising the government on strategies that can be employed to prevent improper application of pesticides in food production and protect the general public from exposure of pesticides. These will ensure permanent access to safe food products by all the consumers and protect them from health effects of pesticides.…”
Section: Resultsmentioning
confidence: 99%
“…There is limited information on health effects associated with pesticide dietary exposure from pesticide contaminated foods in Tanzania, hence efforts need to be taken to generate such information. The only available information was generated by Kariathi et al (2016) whereby they investigated pesticide exposure from fresh tomatoes.…”
Section: Health Effects Of Pesticidesmentioning
confidence: 99%